Urbanization and Its Environmental Impact: Challenges and Mitigation Strategies - Dr Poonam Singh,; Dr Pratiksha Singh,; Dr Richa Singh,; Dr Vibha Parihar,; Dr. Pragya Ojha,; Vanshika Tewari, (The Bioscan, 2025)
This means that the transformation of people from the rural structure to the urban, has been a very regular feature of modern society. As it contributes to economic growth and provides better standards of living the environment faces large problems. Urbanization normally leads to loss of habitat, pollution, resource depletion and, emission of greenhouse gases. It adds to climate change, hostile health conditions and the depletion of ecosystems all around the world. Some of the environmental effects of urbanization include; deforestation, which leads to elimination of natural ecosystems, emissions of gaseous and liquid wastes, overuse of resources and finally poor disposal of wastes. Cities are the primary hotspots of CO2 emission which is contributing to both global warming and worsening many other health challenges within the society, such as respiratory diseases. Third, the conversion of land for urban development is also a problem because it decreases access to water, pollutes it, and lowers the amount of plant and animals that can live in a region. Thus, measures against these negative impacts need to be applied as an offset. Sustainable urban planning which is aimed at practical and conceptual ways of implementing compact city designs, green infrastructure and preventing the phenomenon of the urban sprawl can lessen the loss space for habitation and decrease the levels of contamination. The figures show that incorporating renewable energy systems, optimizing the transportation system for a large number of people, and enhancing energy efficient buildings could minimize carbon emissions. Still, on the environmental impact, efficient disposal of wastes, water efficiency and any infrastructural development must be friendly to climate change. When cities incorporate these measures they are effectively moved towards more sustainable communities, whilst simultaneously promoting economic growth and development and maintaining sustainability of resources as well as stability of ecosystems. This paper holds the view that fruitful practices of urban management if backed by policies and involvement from the society can play a major role in minimizing the so pejorative effects of urbanization.